STRUCTURAL EQUATION MODELLING ON EMPLOYEE PERFORMANCE: EVIDENCE FROM INTRAPRENEURIAL BEHAVIOR AND SOFT SKILLS ANALYSIS - Damayanthy, Dini; Hardyastuti, Suhatmini; Irham, Irham (Universitas Brawijaya, Indonesia, 2020)
Employees are one of the main resources of the organization that has an important role in carrying out activities and determining policies in the organization. Companies need to be able to improve employee performance and create a sustainable competitive advantage. The application of human resource management practices can improve employee performance. But several studies state that intrapreneurial behavior and soft skill also affected it.This study aims to analyze the relationship between human resource management practices, intrapreneurial behavior, and soft skills on the performance of employees working at PT Perkebunan Nusantara XI. The integrated research model was developed by combining three main variables from various literature. Primary data was collected through 150 questionnaires for selected employees working in the head office and production work units. The validity and reliability of the model are tested using by structural equation model. This study was conducted at a state-owned agribusiness organization based on crosssectional data, so it cannot be generalized to a wider range of sectors. The results of this study showed that the variables of human resource management practices and soft skills significantly influence employee performance. The results of the study have the potential to assist policymakers, stakeholders, and organization management in adopting well-articulated findings to improve the quality of human resources and create sustainable competitive advantages. This study contributes to the expansion of literature based on empirical evidence relating to the relationship of human resource management practices, intrapreneurial behavior, and soft skills.